P4_1 Brownian Motors - Davis, Claire; Tilley, Freddie; Hague, Pete (Physics Special Topics, 2011)
The concept of using Brownian motion as a source of energy to power a motor is explored, and the constraints of the system discussed. It is found that when there is a temperature gradient maintained in the system, it may behave as a heat engine and thus does not contradict any of the laws of thermodynamics.